In Hospital Outcome of Patients with Acute St-Elevation Myocardial Infarction Requiring Temporary Pacemaker - Muhammad Khalil, Asma Zafar Khawaja, Shahab Saidullah, Asma Rauf, Nabil Younas, Syed Nasir Ali Shah, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: Acute myocardial infarction is a serious public health concern around the globe and temporary pacing is required in a variety of myocardial infarction. The present study aimed to determine the in-hospital outcome of acute ST elevation myocardial infarction patients requiring a temporary pacemaker. Patients and Methods: This descriptive cross-sectional study was carried out on 120 acute myocardial infarction patients in the Cardiology Unit of PIMS Hospital, Islamabad from January 2021 to March 2023. Each individual underwent chest X-ray, ECG and serum markers. A detailed physical history including age, gender, smoking history, occupation, ischemic heart disease, diabetes, and hypertension were noted in specific designed proforma. Inclusion Criteria: Acute myocardial infarction patients who had chest pain, elevated serum markers, New onset ST Elevation and complete heart block on ECG and required pace maker during their hospitalization were enrolled. Exclusion Crieteria: Complete Heart block due to CKD or electrolyte imbalance, beta blocker or calcium channel blocker overdose, congenital heart block were excluded from the study. Results: The overall mean age was 52.64±6.8 years. The incidence of smokers, diabetes, and hypertension was 76 (63.3%), 56 (46.7%), and 52 (43.3%) respectively. The mean duration of symptom’s onset during hospital admission was 7.9±3.8 hours. About 48 (40%) patients had implanted temporary pacemaker at presentation, 66 (55%) on first post MI day, and 6 (5%) on 2nd post MI day. The in-hospital mortality was 8.3% (n=10). The incidence of ventricular tachycardia, ventricular fibrillation, and asystole was 28.3% (n=34), 3.3% (n=4) and 1.7% (n=2) respectively. Conclusion: The present study found that complete heart block is associated with a poorer early prognosis in individuals with ST-Elevation MI who require temporary pacemaker. In these individuals, a more intensive therapy strategy targeted at reducing early death is required. Keywords: Acute myocardial infarction, in-hospital outcome, temporary pace maker